Impact of Sea Surface Temperature Variability on Pelagic Fisheries Productivity - Rudi Hartono; Sarah Feronica; Yohana Joly (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Sea surface temperature variability is a major driver of change in marine ecosystems and pelagic fisheries productivity. This study analyzes the relationship between SST variability and pelagic fisheries performance using a quantitative longitudinal design. The analysis integrates satellite-based temperature data, fisheries catch records, and ecological indicators over time. The objective is to examine how changes in ocean temperature influence catch levels, catch efficiency, and species distribution patterns. The results show a consistent increase in sea surface temperature variability across the study period. This increase is accompanied by declining stability in pelagic fisheries productivity, particularly in tropical regions. Catch per unit effort and total catch exhibit negative responses to sustained warming conditions. Spatial analysis further reveals significant redistribution of pelagic fish populations, with a gradual shift toward cooler, higher-latitude waters. These changes indicate that marine species are actively tracking suitable thermal habitats. Statistical analysis confirms a significant relationship between SST variability and fisheries productivity. The effects are non-linear, with stronger declines observed beyond specific temperature thresholds. The findings suggest that warming oceans reduce ecosystem stability by disrupting primary productivity and altering food web dynamics. Overall, the study demonstrates that sea surface temperature variability plays a central role in shaping pelagic fisheries outcomes. It affects both the abundance and spatial distribution of marine resources. These results highlight the need for adaptive fisheries management strategies that account for ongoing ocean warming and increasing environmental variability.